High Level of Serum Complement C3 Expression is Associated with Postoperative Vasculopathy Progression in Moyamoya Disease - Wang MJ; Wang J; Zhang H; Hao FB; Gao G; Liu SM; Wang XP; Li JJ; Zou ZX; Guo QB; Fu HG; Han YQ; et al. (Journal of Inflammation Research, 2024)
Min-Jie Wang,1– 3 Jiayu Wang,4 Houdi Zhang,2,3 Fang-Bin Hao,1– 3 Gan Gao,1– 3 Si-Meng Liu,1– 3 Xiao-Peng Wang,1– 3 Jing-Jie Li,1– 3 Zheng-Xing Zou,2,3 Qing-Bao Guo,1– 3 He-Guan Fu,2,3 Yi-Qin Han,2,3 Cong Han,2,3 Lian Duan2,3 1Chinese PLA Medical School, Beijing, People’s Republic of China; 2Department of Neurosurgery, the First Medical Centre, Chinese PLA General Hospital, Beijing, People’s Republic of China; 3Department of Neurosurgery, the Fifth Medical Centre, Chinese PLA General Hospital, Beijing, People’s Republic of China; 4Department of Immunology, Institute of Basic Medical Sciences Chinese Academy of Medical Sciences, School of Basic Medicine Peking Union Medical College, Beijing, People’s Republic of ChinaCorrespondence: Lian Duan; Cong Han, Department of Neurosurgery, Department of Neurosurgery, the Fifth Medical Centre (South Campus), Chinese PLA General Hospital, No. 8 Dong-Da Street, Fengtai District, Beijing, 100071, People’s Republic of China, Tel +86-10-66947389 ; +86-13466346163 ; +86-10-66947388, Fax +86-10-62177976, Email duanlian307@sina.com; hc82225@126.comBackground: The immune system plays an important role in the onset and development of moyamoya disease (MMD), but the specific mechanisms remain unclear. This study aimed to explore the relationship between the expression of complements and immunoglobulin in serum and progression of MMD.Methods: A total of 84 patients with MMD and 70 healthy individuals were enrolled. Serum immunoglobulin and complement C3 and C4 expression were compared between healthy individuals and MMD patients. Follow-up was performed at least 6 months post-operation. Univariate and multivariate analysis after adjusting different covariates were performed to explore predictive factors associated with vasculopathy progression. A nomogram basing on the results of multivariate analysis was established to predict vasculopathy progression.Results: Compared to healthy individuals, MMD patients had significantly lower expression of serum complements C3 (P = 0.003*). Among MMD patients, C3 was significantly lower in those with late-stage disease (P = 0.001*). Of 84 patients, 27/84 (32.1%) patients presented with vasculopathy progression within a median follow-up time of 13.0 months. Age (P=0.006*), diastolic blood pressure (P=0.004*) and serum complement C3 expression (P=0.015*) were associated with vasculopathy progression after adjusting different covariables.Conclusion: Complement C3 is downregulated in moyamoya disease and decreases even further in late–Suzuki stage disease. Age, diastolic blood pressure and serum complement C3 expression are associated with vasculopathy progression, suggesting that the complement might be involved in the development of moyamoya disease.Keywords: moyamoya disease, complement, Suzuki stage, nomogram